2022
DOI: 10.1186/s12968-022-00887-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance imaging and spectroscopy in clinical long-COVID-19 syndrome: a prospective case–control study

Abstract: Background The underlying pathophysiology of post-coronavirus disease 2019 (long-COVID-19) syndrome remains unknown, but increased cardiometabolic demand and state of mitochondrial dysfunction have emerged as candidate mechanisms. Cardiovascular magnetic resonance (CMR) provides insight into pathophysiological mechanisms underlying cardiovascular disease and 31-phosphorus CMR spectroscopy (31P-CMRS) allows non-invasive assessment of the myocardial energetic state. The main aim of the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The need to investigate postinfection sequelae is underlined by incongruence of the data currently available. 1,10 The following novelties were observed in this study:…”
Section: Discussionmentioning
confidence: 81%
“…The need to investigate postinfection sequelae is underlined by incongruence of the data currently available. 1,10 The following novelties were observed in this study:…”
Section: Discussionmentioning
confidence: 81%
“…In a prospective study of 20 patients diagnosed with PASC without underlying CVD, there was no significant difference in myocardial energetics (phosphocreatine to adenosine triphosphate ratio) when compared with matched healthy controls with no prior diagnosis of SARS-CoV-2. 143 Although this small exploratory study did not show a revolutionary difference in myocardial energetics between cases and controls, larger multicenter studies may support the capability of cMRI with spectroscopy to provide insight into energy metabolism and aid in establishing a diagnosis of mitochondrial dysfunction in individuals with CV PASC.…”
Section: Proposed Diagnostic and Therapeutic Strategies For CV Pascmentioning
confidence: 73%
“… 47 Indeed, several studies have reported that approximately 20-30% of their patient populations experience myocardial fibrosis after recovery from acute SARS-CoV-2 infection. 47 , 48 , For example, in a prospective study of 159 patients hospitalized with COVID-19, Morrow et al found that one in five patients had evidence of myocardial fibrosis 28-60 days post-discharge. 47 Similarly, 21% of patients in another investigation were observed to have LGE indicative of myocardial fibrosis 6 months after ICU admission.…”
Section: Cardiac Dysautonomia and Arrhythmiasmentioning
confidence: 99%